Respuesta :
Answer: -56
Step-by-step explanation: if u take -35/5 u get -7 so x=-7 so then u get -28+4(-7) so 4 times -7 equals -28 so -28 + -28= -56
Answer:
-56
Step-by-step explanation:
First, let's solve for x in 5x = -35.
Step 1: Divide both sides by 5.
- [tex]\frac{5x}{5} = \frac{-35}{5}[/tex]
- [tex]x = -7[/tex]
Now, that we know the value of x is equal to -7, let's simplify the expression -28 + 4x:
- [tex]-28 + 4(-7)[/tex]
- [tex]-28 - 28[/tex]
- [tex]-56[/tex]
Therefore, the value of -28 + 4x is equal to -56 when x is equal to -7.